Aging in the Asian 'Tigers' : Challenges for Fiscal Policy - Heller, Peter (Washington, D.C. : International Monetary Fund, 1997)
The paper assesses the government expenditure effects from changing demographics in the Asian 'Tiger' economies through 2050. With some exceptions, their limited social insurance commitments initially suggest that aging populations may not adversely affect fiscal balances. Yet for all the Tigers, changing illness patterns and medical modernization may combine with demographics to intensify budgetary pressures. The paper notes the implications of the Tigers' reliance on private sector pension and medical insurance systems; the need for an active public role; and the complications for fiscal analysis when private sector instruments are used, in a mandatory way, as public policy instruments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet